ANALISIS PENGARUH ISLAMIC CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi kasus pada Bank Syariah di Asia) - Adiertanto, Charles Pramudita; Chariri, Anis (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the characteristic factors of Islamic CorporateGovernance in Islamic banks in Asia region that can affect the disclosure of corporatesocial responsibility (CSR) in the Annual Reports of Islamic banks. These characteristicfactors such as Islamic Governance (including the presence of the supervisory board,composition Islamic sharia supervisory board skills), the size of board of commissioners,independent commissioners, board of commissioners meeting, size of the audit committee,audit committee independence, audit committee meetings and profitability.Populations of this research are the Islamic banks in Asia, overall the sampleconsists of seven sharia banks which are the members of AAOIFI and three (3) Islamicbanks in Indonesia which are not yet become a members, but have adopted regulations andstandards arranged by AAOFI. So that there are 10 Islamic banks in the sample with 50annual reports that are determined through purposive sampling. This study analyzed theannual reports of Islamic banks with a panel method analysis. Data analysis wasperformed with the classical assumption test and hypothesis testing using multiple linearregression method.The results of this study indicate that of the eight independent variables, sevenvariables affect the disclosure of CSR, but the four variables (composition of independentcommissioners, board of commissioners meeting, the size of board of commissioners,composition of audit committee independence) has a negative coefficient so the hypothesisis rejected four variables and the third variable (Islamic Governance, the size of board ofcommissioners, audit committee meetings ) positively influence the level of CSR disclosure.While the profitability variable is not a positive influence on the level of CSR disclosure.